2004
DOI: 10.1001/archinte.164.13.1445
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Model for Predicting Hypoglycemia in Type 2 Diabetes Mellitus

Abstract: Self-monitoring of blood glucose is superior to hemoglobin A1c measurement in predicting long-term hypoglycemia in persons with type 2 diabetes. The risk of hypoglycemia associated with treatment intensification may be offset by strategies that reduce glucose variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 16 publications
2
39
0
1
Order By: Relevance
“…Similarly, poorer b-cell function on OGTT was associated with increased glycemic variability in participants spanning the spectrum of glucose tolerance from normal to prediabetes to T2DM (19). Finally, this relationship is further supported by evidence that increased glycemic variability (rather than the absolute level of glycemia) may be an important determinant of the risk of hypoglycemia, implicating diminished capacity of the b-cells (or islets) to regulate glucose levels from straying either above or below the normal range (14)(15)(16). Against this background, the current study extends this literature by demonstrating that glycemic variability in early T2DM is modifiable and can be reduced by improving b-cell function with short-term IIT.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, poorer b-cell function on OGTT was associated with increased glycemic variability in participants spanning the spectrum of glucose tolerance from normal to prediabetes to T2DM (19). Finally, this relationship is further supported by evidence that increased glycemic variability (rather than the absolute level of glycemia) may be an important determinant of the risk of hypoglycemia, implicating diminished capacity of the b-cells (or islets) to regulate glucose levels from straying either above or below the normal range (14)(15)(16). Against this background, the current study extends this literature by demonstrating that glycemic variability in early T2DM is modifiable and can be reduced by improving b-cell function with short-term IIT.…”
Section: Discussionmentioning
confidence: 83%
“…However, although some studies have reported that increased glycemic variability may be associated with the incidence of diabetic retinopathy (6,7), diabetic neuropathy (8), and coronary artery calcification (9) in patients with T2DM and type 1 diabetes (T1DM), other studies have not supported this association (10)(11)(12). Nevertheless, although its relevance to vascular complications remains uncertain (13), at a given level of glycemia, increased glucose variability raises the risk of hypoglycemia (14)(15)(16) and, hence, is clinically important.…”
mentioning
confidence: 99%
“…Diyabetik diyaliz hastalarında, yüksek HbA1c ve uzun dönem glisemik dalgalanmalar hipoglisemi ile ilişkili hastaneye yatış riskinde artışa neden olmaktadır. 25 Williams ve ark.nın yaptıkları çalışmada HD tedavisine yeni başlayan diyabetik hastalar üç yıl boyunca takip edilmiş ve hipoglisemi nedeni ile hastaneye yatan hastaların oranı %4,1 olarak bulunurken, HbA1c düzeyi arttıkça hipoglisemiye bağlı hastaneye yatış riskinde artış saptanmıştır. Üç yıllık HbA1c takipleri sonucunda HbA1c dü-zeyi arttıkça SD'nin arttığı ve SD'deki artışın da hipoglisemiye bağlı hastaneye yatış riskini artır-dığı gösterilmiştir.…”
Section: Gli̇semi̇k Dalgalanma Ve Di̇yabeti̇k Kompli̇kasyon İli̇şki̇si̇unclassified
“…Both Cox, et al and The Diabetes Outcome in Veterans Study (DOVES) suggested that glycemic variability may be a potential predictor of future hypoglycemia occurrence. 48,49 Furthermore, glycemic variability if accompanied with severe hypoglycemia episodes may adversely alter the prognosis of acutely ill patients 50,51 It has also been shown that hyperglycemia after hypoglycemia could be more hazardous than that when hypoglycemia is followed by normoglycemia. 52 One can argue that much of risk in long-term microvascular and macrovascular complications could be avoided by focusing merely in reduction of hypoglycemic episodes.…”
Section: Glycemic Variability and Hypoglycemia Complica-tionsmentioning
confidence: 99%